Chiral Ratio of the Compressional and Shear Velocity for the Determination of Strong Earthquake Magnitudes through High-Frequency Energy Radiation - Torres-Silva, H.; Torres-Cabezas, D.; López-Bonilla, J.; Tuladhar, B.M. (Kathmandu University Journal of Science, Engineering and Technology, 2015)
In this short paper, we define and determine the connection between an electromagnetic chiral theory and the Hara’s relation (high-frequency energy radiation from the arrival time of a P-wave) under a chiral approach, considering the possibility that gravity breaks parity, with left and right handed gravitons coupling to matter with a different Newton’s constant. We show that this would affect the earth dynamics and induce strong earthquakes. This theory allows us to determine chiral changes on the ratio of the compressional velocity to the shear velocity for the estimation of earthquake magnitudes. Through measurements of high-frequency energy radiation, it is possible to determine the amplitude of strong earthquakes as occurred in Chile and Japan recently. On April 25, 2015, Saturday, a strong local magnitude 7.8 on the Richter scale earthquake hit the west side of Nepal in the area Barpak, Gorkha district, between the capital Kathmandu and tourist town Pokhara. This earthquake was followed by many powerful aftershocks, and an unexpected aftershock of local magnitude 6.8 on the Richter scale hit the east side of Nepal in the area Dolkha on Tuesday, May 12. The earthquakes caused extensive damage to buildings and thousands of deaths and injuries and were even felt in Pakistan, India, and Bangladesh. No radiation data is obtained from the Nepal earthquake 2015. Our proposed theory can also be applied for this case.